U.S. Responses to the Canadian Industrial Disputes Investigation Act - Ramirez, Bruno (Relations industrielles / Industrial Relations, 1974)
The author analyses the impact that the Canadian Industrial Disputes Investigation Act of 1907 had in the U.S. His article also tries to show the extent to which the question of arbitration tended to transcend the narrow boundaries of industrial relations practice and acquire a wider political significance.